2012
DOI: 10.1161/strokeaha.112.671982
|View full text |Cite
|
Sign up to set email alerts
|

Nonadditive Neuroprotection With Early Glutamate Receptor Blockade and Delayed Hypothermia After Asphyxia in Preterm Fetal Sheep

Abstract: Plasma samples were taken during and after UCO. Fetal extradural and esophageal temperatures, mean arterial blood pressure, and Background and Purpose-Hypothermia induced after perinatal hypoxia-ischemia is partially protective. This study examined whether early treatment with the noncompetitive N-methyl-d-aspartate receptor antagonist, dizocilpine, can augment neuroprotection with delayed hypothermia after severe asphyxia in preterm fetal sheep at 0.7 weeks gestation (equivalent to 28-32 weeks in humans). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…Moreover, we found that delayed hypothermia partially protected the CA3 region but that early treatment with HET0016 did not significantly augment the hypothermic protection. Likewise, early treatment with an N-methyl-D-aspartate receptor antagonist failed to augment neuroprotection afforded by delayed hypothermia in the CA3 region in preterm fetal sheep [41]. HET0016 is capable of partially protecting rodent hippocampal slice cultures from oxygen-glucose deprivation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that delayed hypothermia partially protected the CA3 region but that early treatment with HET0016 did not significantly augment the hypothermic protection. Likewise, early treatment with an N-methyl-D-aspartate receptor antagonist failed to augment neuroprotection afforded by delayed hypothermia in the CA3 region in preterm fetal sheep [41]. HET0016 is capable of partially protecting rodent hippocampal slice cultures from oxygen-glucose deprivation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although hypoxia-ischemia appears to trigger accumulation of glutamate in the extracellular space, glutamate receptor blockade rendered only partial neuroprotection after severe preterm hypoxia-ischemia (George et al 2012). This is consistent with findings that acute WMI is characterized by a spectrum of necrotic and apoptotic preOL degeneration (Alix et al 2012).…”
Section: Cellular-molecular Mechanisms Of Acute Wmimentioning
confidence: 99%
“…At the end of cooling, fetuses were allowed to rewarm spontaneously. Cooling was induced by circulating cold water (10ºC) through the cooling coil around the fetal body, 2 and was titrated in the first 2 hours to reduce fetal extradural temperature from 39.4 ± 0.1ºC to between 36 and 37ºC. Seven days after occlusion the ewes and fetuses were killed by an overdose of sodium pentobarbitone (9 g, i.v.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…1 Early electroencephalographic (EEG) monitoring is predictive of long-term outcome after perinatal hypoxia-ischemia at term, 2 but the effect of mild hypothermia on EEG recovery in preterm infants is unknown. In normal humans, mild hypothermia (to ≈33.5°C) is associated with a small reduction in EEG amplitude, with a minor shift in frequencies to theta and beta activity.…”
mentioning
confidence: 99%